2020
DOI: 10.21203/rs.3.rs-87258/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Malaria Parasite Detection in Thick Blood Smear Microscopic Images Using Modified YOLOV3 and YOLOV4 Models

Abstract: Background Information: Manual microscopic examination is still the ”golden standard” for malaria diagnosis. The challenge in the manual microscopy is the fact that its accuracy, consistency and speed of diagnosis depends on the skill of the laboratory technician. It is difficult to get highly skilled laboratory technicians in the remote areas of developing countries. In order to alleviate this problem, in this paper, we propose and investigate the state-of-the-art one-stage and two-stage object detection algori… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…From this table, it is demonstrated that the proposed method outperforms the existing techniques in terms of accuracy, training time, and prediction speed. Reference Accuracy (%) [36] 97.00 [19] 97.30 [16] 97.47 [17] 97.70 Ours 99.67…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…From this table, it is demonstrated that the proposed method outperforms the existing techniques in terms of accuracy, training time, and prediction speed. Reference Accuracy (%) [36] 97.00 [19] 97.30 [16] 97.47 [17] 97.70 Ours 99.67…”
Section: Methodsmentioning
confidence: 98%
“…Several studies have been proposed for malaria blood smear detection, segmentation, and classification [16,17]. Quan et al [18] utilized 27,558 malaria blood smear images from the National Institute of Health (NIH) and expanded wielding rotation, zooming, and flipping.…”
Section: Figure 1: Cycle Of Microbe To Mosquito Transmissionmentioning
confidence: 99%
“…Another study by [37] proposes an ensemble of pretrained and custom CNN models for classification of infected and uninfected RBC cells segmented from thin blood smear microscopic images. In [38], [39] modified versions of YoloV3 and YoloV4 models are proposed to improve P. falciparum detection capability of SOTA deep learning models on thick smear microscopic images and to make detection models lightweight to be integrated with mobile phone-based diagnosis application.…”
Section: Related Workmentioning
confidence: 99%
“…In this study, three different YOLOV4 based object detection models were evaluated to identify the best model with an optimal trade-off between detection performance and inference speed. The first detection network, which is called YOLOV4-MOD, is based on previous work [39] which is modified to improve small object detection performance of the original YOLOV4 model with minimal computation cost. This model has a large number of trainable parameters and more convolution layers.…”
Section: Proposed Detection Networkmentioning
confidence: 99%
See 1 more Smart Citation